PEMADATAN TANAH AKIBAT PENYARADAN KAYU DENGAN TRAKTOR CATTERPILLAR D7G DI AREAL HUTAN PRODUKSI PT INHUTANI II, KALIMANTAN UTARA - Muhdi (Talenta Publisher, 2016)
This research was aimed to study the soil compaction caused by tractor skidding of Caterpillar D7G) in forest concession area of PT Inhutani II, North Kalimantan. The research showed that the bulk density at conventional timber harvesting after skidding of deepness 0-5 cm, 10-15 cm and 25-30 cm was 1.248 g/cm3; 1.253 g/cm3 and 1.225 g/cm3 respectively. The bulk density at reduced impact logging after skidding of deepness 0-5 cm, 10-15 cm and 25-30 cm was 1.090 g/cm3; 1.084 g/cm3 and 1.038 g/cm3 (respectively. This research indicated that the bulk density at RIL was lower than conventional timber harvesting.